ANALISIS TINGKAT AKURASI MODEL ALTMAN Z-SCORE, INDEKS KEPAILITAN, DAN INDEKS IN05 SEBAGAI PREDIKTOR KEBANGKRUTAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011-2015 - Diana Novita (Universitas Negeri Padang, 2018)
This study discusses the use of bankruptcy prediction model that does not exist applied in Indonesia and determine the accuracy of each model. The research objective is to analyze the differences in outcome prediction and know the model that has the best accuracy level between the model Altman Z-Score, Bankruptcy Index, and IN05 Index. This type of research is a comparative study, the population of all manufacturing companies listed on the Indonesia Stock Exchange in 2011 to 2015. The sample is determined by purposive sampling method so acquired 28 companies, and the total sample is 140 years old company. Data used is secondary data obtained from the official website of Indonesia Stock Exchange (www.idx.co.id). The analytical method used is the analysis of different test-independent k-sample test, descriptive statistics and the accuracy of the model using post hoc test and the type of error. The results show that: 1) there are significant differences between the model of the Altman Z-Score model Insolvency Index, and models IN05 index on manufacturing companies listed on the Stock Exchange. 2) The model has the best accuracy by post hoc test is a model of the Altman Z-Score and by type of error is the most accurate models are models IN05 index.Keywords: Altman Z-Score, Insolvency Index, IN05, Bankruptcy